PERTIMBANGAN HAKIM DALAM MENJATUHKAN PUTUSAN PEMIDANAAN PADA PERKARA PERSETUBUHAN SEDARAH DALAM PUTUSAN NOMOR: 27/PID.SUS/2023/PN.MME - Adira Aulia Jasminingrum; Ismawati Septiningsih (Sebelas Maret University, 2026)
The research in this paper aims to find out whether the judge's considerations at the trial of incestuous sexual relations were in accordance with verdict Number: 27/Pid.Sus/2023/PN.Mme. This research is normative legal research which aims to examine and analyze the verdict on imprisonment and fines in cases of incest in verdict Number: 27/Pid.Sus/2023/PN.Mme in order to ascertain whether the results of the application of the law in this case are appropriate or not in accordance with the provisions of statutory regulations. The results of this research show that the judge's decision in imposing prison sentences and fines in case Number: 27/Pid.Sus/2023/PN.Mme refers to Law Number 17 of 2016 Article 81 paragraph 1, the perpetrator is still a close family member, but committed sexual intercourse thereby violating child protection laws. The verdict given by the judge is to provide a deterrent effect to the perpetrator and the community so that something similar does not happen.